1998
DOI: 10.1159/000018677
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Stapled and Hand-Sewn Anastomoses in Crohn’s Disease

Abstract: Sixty-eight patients with Crohn’s disease who underwent intestinal resection were randomly divided into 2 groups: the stapled group (32 patients, 40 anastomoses) with functional end-to-end anastomoses made with linear staplers and with circular stapling anastomoses, and the hand-sewn group (36 patients, 48 anastomoses), with anastomoses achieved by layer-to-layer suturing. There were no significant differences in operative indications, age, sex, blood loss, or length of hospital stay between the groups. The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 5 publications
0
16
1
1
Order By: Relevance
“…The groups were similar with the exception of mean follow-up (20 vs. 35 months) which may account for the difference in the symptomatic recurrence rates of 18% in the stapled and 48% in the sutured group. Two other studies have reported similar findings [8,9]. On the other hand, two other studies have found no difference in recurrence rates when the data were analyzed actuarially [10,11].…”
Section: Bowel Resectionmentioning
confidence: 64%
“…The groups were similar with the exception of mean follow-up (20 vs. 35 months) which may account for the difference in the symptomatic recurrence rates of 18% in the stapled and 48% in the sutured group. Two other studies have reported similar findings [8,9]. On the other hand, two other studies have found no difference in recurrence rates when the data were analyzed actuarially [10,11].…”
Section: Bowel Resectionmentioning
confidence: 64%
“…The development of stapling devices has decreased the technical difficulty of colorectal surgery and the time required [14][15][16] for the construction of low colorectal anastomoses. These devices allow an anastomosis to be created consistently where one could not be constructed 17 with suturing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the operation time for patients in the staple group tended to be shorter than that for patients in the hand-sewn group, and postoperative complications did not significantly differ between groups [7]. There was no statistically significant difference in the recurrence of Crohn’s disease at the anastomotic site at the median follow-up of 4.5 years (3 patients with recurrence in the staple group vs. 8 in the hand-sewn group).…”
Section: Discussionmentioning
confidence: 99%
“…However, these results suggest that stapling is not hazardous. In fact, it shortens the operating time, decreases blood loss, and improves the patient’s quality of life [7]. …”
Section: Discussionmentioning
confidence: 99%